The assessment of plasma fatty acid profiles in newly diagnosed treatment-naive paediatric Crohn's disease - Schwarz, Jan; Vecka, Marek; Stožický, František; Pomahačová, Renata; Staňková, Barbora; Tvrzická, Eva; Kreslová, Marcela; Zahálková, Romana; Sýkora, Josef (Physiological research, 2021)
Fatty acid (FA) profiles as potentially relevant components of Crohn's disease (CD) have been insufficiently analysed. We sought to explore the plasma profiles of n-3 and n-6 polyunsa-turated fatty acids (PUFAs) in newly diagnosed untreated active CD. We included 26 consecutive CD pediatric patients (<19 years) and 14 healthy controls (HCs). Disease characteristics, including inflammatory markers, dietary histories, and the Pediatric Crohn's Disease Activity Index (PCDAI), were obtained. The profiles of plasma FAs in plasma lipid classes were analysed by gas chromatography with FID detection of methyl esters. The erythrocyte sedimentation rate, C-reactive protein level and fecal calprotectin level (all p<0.001) were significantly higher in CD patients than in HCs. Most changes were observed in plasma phospholipids (PLs), such as a higher content of n-3 and changes in n-6 long-chain PUFAs in the CD group. The CD group had a lower ratio of n-6/n-3 PUFAs in PLs (p<0.001) and triacylglycerols (TAGs) (p<0.01). Correlations of the FA content in plasma PLs with disease activity scores of CD were also observed, which were positive for the sum of monounsaturated fatty acids (MUFAs) as well as oleic acid (18:1n-9) (both p<0.05). The metabolism of PUFAs is significantly altered even in treatment-naive newly diagnosed active pediatric CD, and the content of major FAs in PLs correlates with disease activity and inflammatory markers, thus probably contributing to the still unclear early disease pathogenesis.
Keywords: Adolescent; stupeň závažnosti nemoci; Crohn Disease; Severity of Illness Index; Fatty Acids; lidé; Prospective Studies; Diet; prospektivní studie; studie případů a kontrol; Female; dieta; Male; ženské pohlaví; Case-Control Studies; Humans; mužské pohlaví; mastné kyseliny; Crohnova nemoc; mladiství